Kvinnornas Byggnad (Kvindernes Bygning) - Detaljmodell - (:unkn) unknown (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik, 2025)
The women's building in Copenhagen was commissioned by the danish women's organisation (Kvindernes samfund) and built in 1936. Its original purpose was to serve as a meeting place for women and other women's organisations. When it was built it had amenities such as a restaurant, meeting rooms and halls as well as rooms for hotel use.
Copenhagen Women's building - Detail model
Keywords: Women's building; Functionalism; Organisational building